A Two Way Validation Framework for Cloud Storage Security - Jyothi, Anantula; Indira, Baddam (International Journal of Engineering and Technology, 2018)
High Performance Computing (HPC) has become one of the predominant techniques for processing the large scale applications. Cloud environment has been chosen to provide the required services and to process these high demand applications. Management of such Â Â Â Â Â Â Â Â Â Â Â applications challenges us on three major things i.e. network feasibility, computational feasibility and data security. Several research endeavours are focused on network load and computing cloud date and provided better outcomes. Still those approaches are not able to provide standard mechanisms in view of data security. On the other side, research towards enabling the auditing features on the cloud based data by various researchers has been addressed but their performance is poor. However, the complexity of the audit process proven to be the bottleneck in improving performance of the application as it consumes the computational resources of the same application. Henceforth, this work proposes a novel framework for cloud data auditing at multiple levels to audit the access requests and upon Â Â Â Â Â Â Â Â Â Â Â Â validating the conditions of one level, the connection request will be moved to the further complex levels in order to reduce the Â Â Â Â Â Â Â Â Â Â Â Â Â computational loads. The proposed framework determines a substantial reduction in the computational load on the cloud server, thus improves the application performance leveraging the infrastructure use.Â